Strategic Marketing Management Influence on Making E-Commerce Promotions (International Journal of Scientific Research and Management (IJSRM), 2022)
The paper has highlighted the impact of strategic marketing management on e-commerce promotions. It has been evident that from the very beginning the world is flooded with a variety of businesses and the objectives are to appeal to the customers with different marketing strategies to entice their attention. A business will generate substantial revenues if the marketing management strategies are influencing its overall productivity. In this regard, this paper accumulates the implications of strategic management and marketing approaches on e-commerce promotion from a number of business ventures in general. An organization can thrive in the competitive market only when the strategic approach developed by the company can be presented in such a way that the audience gets attracted to it and reach for it. In such aspects, drawing their attention through e-commerce promotion is an effective tool to boost sales margins. But most of the time organization faces issues due to unstable or improper development of strategic marketing practices. For the development of a business not only its product or services matter but also the environment, customer, and technology matter play a crucial role. When the issues regarding these attributes are mitigated then only positive impacts arise for the e-commerce promotion of any business.